Global Networks of Symbiodinium-Bacteria Within the Coral Holobiont - Bernasconi, R.; Stat, Michael; Koenders, A.; Huggett, M. (Springer, 2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. Scleractinian corals form the framework of coral reefs and host abundant and diverse microbial communities that are fundamental to their success. A very limited number of studies have examined the co-occurrence of multiple partners within the coral ‘holobiont’ and their pattern of specificity over different geographical scales. In this study, we explored two molecular sequence datasets representing associations between corals and dinoflagellates in the genus Symbiodinium and between corals and bacteria, across the globe. Through a network theory approach, we characterised patterns of co-occurrences between bacteria and Symbiodinium with 13 coral genera across six water basins. The majority of the bacteria-Symbiodinium co-occurrences were specific to either a coral genus or water basin, emphasising both coral host and environment as important factors driving the diversity of coral assemblages. Yet, results also identified bacteria and Symbiodinium that were shared by multiple coral genera across several water basins. The analyses indicate that shared co-occurrences are independent of the phylogenetic and biogeographic relationship of coral hosts.